1981
DOI: 10.1152/ajpheart.1981.240.3.h348
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary injury and prostaglandin production during endotoxemia in conscious sheep

Abstract: Prostaglandins F2 alpha, E2, and I2 (as 6-keto-PGF1 alpha) and TxA2 (as TxB2) were measured by radioimmunoassay in plasma and lymph from 12 conscious sheep with chronic lung lymph fistulas given Escherichia coli endotoxin (2-10 micrograms/kg) and followed for 24 h. Endotoxin produced a two-phase pulmonary injury. Phase 1 was characterized by transient severe pulmonary hypertension and increased lymph flow rate (QL). Plasma and lymph PGF2 alpha concentrations increased from base-line values of 0.13 +/- 0.08 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
2

Year Published

1983
1983
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 0 publications
5
57
0
2
Order By: Relevance
“…It is well known that even brief periods of endotoxaemia in the pig are associated with a substantial, biphasic rise in MPAP and PVR ), which in turn accounts for the observed fall in CO. This biphasic rise in MPAP and PVR is due to the formation of the vasoconstrictor thromboxane A2 (first phase) (Hardie & Olson, 1987;Leeper-Woodford et al, 1981;Weitzberg et al, 1993), as well as the development of a pulmonary oedema (second phase) (Demling et al, 1981). These pathophysiological alterations in MPAP and PVR during the acute phase of endotoxaemia are peculiar to this species and have not been described in man (Parillo et al, 1990).…”
Section: Mortalitymentioning
confidence: 96%
See 1 more Smart Citation
“…It is well known that even brief periods of endotoxaemia in the pig are associated with a substantial, biphasic rise in MPAP and PVR ), which in turn accounts for the observed fall in CO. This biphasic rise in MPAP and PVR is due to the formation of the vasoconstrictor thromboxane A2 (first phase) (Hardie & Olson, 1987;Leeper-Woodford et al, 1981;Weitzberg et al, 1993), as well as the development of a pulmonary oedema (second phase) (Demling et al, 1981). These pathophysiological alterations in MPAP and PVR during the acute phase of endotoxaemia are peculiar to this species and have not been described in man (Parillo et al, 1990).…”
Section: Mortalitymentioning
confidence: 96%
“…In contrast to the systemic vasodilatation, pulmonary hypertension often occurs in the acute phase of endotoxaemia. This may lead to rightsided heart failure, pulmonary oedema, hypoxia and death (Zapol et al, 1977;Demling et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated increased plasma thromboxane B2 (TXB2) levels in response to endotoxin (Cook et al, 1980;Frolich et al, 1980;Harris et al, 1980;Demling et al, 1981). TXB2 is the stable metabolite of TXA2, a potent vasoconstrictor and proaggregatory substance synthesized by a variety of cells (Moncada & Vane, 1979) including platelets and macrophages (Cook et al, 1981a), which are target cells for endotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated increased plasma thromboxane (Tx)B2, the stable metabolite of TxA2, in response to endotoxin (Cook, Wise & Halushka 1980;Frolich Ogletree, Peskar & Brigham 1980;Harris, Zmudka, Maddox, Ramwell & Fletcher 1980;Demling, Smith, Gunther, Flynn & Gee 1981;Coker, Hughes, Parratt, Rodgers & Zeilin 1981). TxA2 is a potent vasoconstrictor and proaggregatory substance synthesized by a variety of cells including platelets (Moncada & Vane, 1979) and macrophages (Cook, Wise, Knapp & Halushka, 1981a;Feuerstein, Foegh & Ramwell, 1981), which are target cells for endotoxin.…”
Section: Introductionmentioning
confidence: 99%